Taxation and Investment in Colombia - Perret, Sarah (OECD Economics Department Working Papers, 2015)
The Colombian corporate tax system is highly complex and distortive. The effective tax burden on businesses is very high due to the combined effect of the corporate income tax, the corporate surtax introduced in 2012 (CREE), the net wealth tax on business assets and the value added tax (VAT) on fixed assets. Indeed, in addition to high statutory taxes on corporate income, formal sector businesses are subject to a wealth tax on their net assets and to a production-based VAT system under which VAT paid on the purchases of fixed assets is not creditable against output VAT. Calculations in this paper find that the total marginal effective tax rate reaches about 60% for equity-financed investments. Such a high effective corporate tax burden is likely to deter investment and to further encourage tax evasion in the future and therefore calls for a fundamental business tax reform. This paper also reviews the other key elements of the capital income tax system in Colombia. This Working Paper relates to the 2014 OECD Economic Survey of Colombia (www.oecd.org/eco/surveys/economic-survey-colombia.htm)